Wiersz Marty Podgórnik. Próba dotarcia do poetyckiej receptury = Marta Podgórnik`s Poem. An Attempt to Reach the Poetic Formula - Szott, Mirosława (1987- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Does Marta Podgórnik have a recipe for creating poetry? She certainly has her own unique style of combining words, creating rhythm and connotations. She is among the most prominent poets of the contemporary literature scene in Poland. In the article I examine four aspects of her poetic language, trying to uncover the linguistic formula used by her to convey her truth about the world. These four aspects are among her favorite tools: enjambment, rhyme, vulgarity and intertextuality as a building element of the text`s meaning.
Keywords: Podgórnik, Marta (1979- ); przerzutnia; rym; wulgaryzm; intertekstualność; poezja polska - od 1989 r.; enjambment; rhyme; vulgarity; intertextuality; polish poetry